STRATEGI PIMPINAN DALAM PENINGKATANBUDAYA KERJA DI PERGURUAN TINGGI - Rohmah, Noer (J-MPI (Jurnal Manajemen Pendidikan Islam), 2016)
The college is one of the dominant social institutions and the effect on the culture of a nation is also responsible for the transmission of culture from one generation to another as well as preservation. Universities at this time to be ready to face the challenges of globalization and produce graduates who can compete and fill the global era. For that universities must be able to become an institution that global perspective as well as the resources of international standard. Therefore, it is necessary to change the mindset of college becomes mindset following the change, which is oriented on creating a work culture that is more dynamic, productive, and competitive. As for some of the strategies that can be taken by the leadership for the improvement of work culture to make it more dynamic and competitive of them are; (1) creating a smart cultural organization, (2) build employee morale order dynamic competition, (3) improve emotional intelligence in building relationships work, and (4) improve communication in relationships creating work team.